Complicities : The Intellectual and Apartheid - Sanders, Mark, 1968- (Book collections on Project MUSE., 2002)
A theoretically informed study of five major pro- and anti-apartheid intellectuals, showing the inevitability of complex and compromised positions, and the impossibility of pure ones.